(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper aims at discussing various practical aspects of industrial relation of a selected three tea garden of Charaideo district. To make the discussion systematic, entire paper is devided into three parts. The first part entitles the theoretical approach includes an introduction, meaning of industrial relation, objectives, methodology, location and limitation of the study. The second part entitled “Industrial relation practices of tea industry of Assam” provides a comprehensive study on various aspects of industrial relation of three selected tea Garden of Charaideo district. In this permanently attempt will be take to discuss union management relation, worker participation in management, negotiating, collective bargaining, grievances handling procedure, disciplinery action, settlement of industrial dispute etc.. Third part entitled to conclusion where some major suitable suggestions will be put forwarded with a view to removing the problems and to make the position of industrial relations of the selected three tea gardens sound.